Performance of Pulses in Pulse-Finger Millet Relay Chopping Systems as Influenced by Establishment Times of Relayed Millet and N Levels to Legumes - Purushotham, S; Shivshankar, K (Annals of Arid Zone, 2016)
A field experiment was conducted at Agricultural Research Station, Chintamani (Karnataka State) during 1982 and 1983 under dry land conditions to study the performance of three legumes (soyabean, cowpea and fields beans) as early crops at three N levels (0, 12.5 and 25 kg N/ha) and with establishment of finger millet at two times (30 and 60 days after sowing of legumes). The pooled grain and haulm yields of soybean were significantly higher at later establishment (718 and 618 kg/ha than at early establishment, 388 and 510 kg/ha. Yield differences of cowpea and field beans were non-significant due to establishment times. The total N uptake by soybean was significantly higher in later establishment (61.8 kg N/ha as compared to establishments of millet 07.3 kg N/ha) in second year, In cowpea and field beans, the total N uptake was relatively higher in the later establishment. Soybean and cowpea car be preferred as early crops as these are short in stature and mature earlier than field beans and that legumes in the relay cropping system need not b fertilized with N.